Towhee get your gun - Ripley, J. R., 1955- (Ripley, J. R., 1955- Bird lover's mystery., 2019)
"Who's got time for birdwatching? Amy has enough to do running her shop, fighting attempts by the town planning commission to demolish her old Victorian house, and rescuing an injured towhee. Yet somehow she allows herself to get roped into performing in the Ruby Lake, North Carolina, community theater's new musical after some cast members get injured by mysterious mishaps. The production seems plagued by bad luck, but events turn tragic when a member of the company is found murdered in a locked dressing room. Trading in her binoculars for a magnifying glass, Amy steps into the role of amateur sleuth and soon discovers the victim ruffled a lot of feathers. With a flock of suspects, Amy will need to beat the bushes before the cagey killer takes flight. After all, the show must go on.."